How do we build ourselves from memory? español - Ortiz Zambrano, Gabriela Belén (2019)
This essay reflect on the process that my students performed during the course of reading, writing and analysis based on the resolution of the question: Who were my ancestors? The present text, stops in two moments. The first explains how the collective memory from the meeting of the different testimonies is constituted, and at the same time, it composes the group of adolescents from their findings. In the second moment of analysis, we focus on how they think and rebuild having worked this "other" past from their own memory and that of their relatives.